Soluble ST2 protein as a new biomarker in patientswith precapillary pulmonary hypertension - Marta Banaszkiewicz; Arkadiusz Pietrasik; Szymon Darocha; Michał Piłka; Michał Florczyk; Anna Dobosiewicz; Piotr Kędzierski; Ewa Pędzich-Placha; Janusz Kochman; Grzegorz Opolski; Adam Torbicki; Marcin Kurzyna (Archives of Medical Science)
Introduction Non-invasive tests that may improve clinical evaluation of pulmonary hypertension (PH) are needed. The purpose of this study was to assess the role of soluble ST2 (sST2) in patients with PH.